2011
DOI: 10.1186/1749-8090-6-116
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal Perforation: A diagnostic and therapeutic challenge in a resource limited setting. A report of three cases

Abstract: BackgroundOesophageal perforation is a condition associated with a high mortality. Its management is still controversial with operative treatment being favoured but a shift to conservative management is occurring. Very little exists in medical literature about its management in Sub-Saharan Africa, where the paucity of thoracic surgeons is compounded by limited diagnostic and therapeutic facilities.Case PresentationWe report three cases of oesophageal perforation which were all treated conservatively with tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…[ 3 4 ] There have been reports of higher complications in academic training/teaching institute, emergency procedure, and institute with low patient volume. [ 2 3 5 ] Though instrumentation is the common cause of esophageal injury, sharp object impaction or retrieval (33%) has the highest complication rate which has been reconfirmed in our series also. [ 1 4 ] Site of perforation may be anywhere from cervical to abdominal esophagus.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…[ 3 4 ] There have been reports of higher complications in academic training/teaching institute, emergency procedure, and institute with low patient volume. [ 2 3 5 ] Though instrumentation is the common cause of esophageal injury, sharp object impaction or retrieval (33%) has the highest complication rate which has been reconfirmed in our series also. [ 1 4 ] Site of perforation may be anywhere from cervical to abdominal esophagus.…”
Section: Discussionsupporting
confidence: 71%
“…Five children with corrosive strictures presented within 3 weeks of ingestion while the remaining two had ingested more than 3 months back. Contrast study and endoscopy revealed single (4) or multiple strictures (3); varied size (5 mm in 2 , 1 cm 2 , 1.5 cm 1 , 5 cm 1 ), and site (cricopharynx 2 , middle one-third 2 , lower one-third 5 ) and near complete obstruction (2). Children with severe stricture (2) had gastrostomy, followed by retrograde and ante grade dilatation under endoscopic guidance by the gastroenterologist.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In case oesophageal rupture is suspected, the best option to confirm it is contrast esophagography [ 12 ]. Diagnosis of oesophageal rupture is not straightforward; it is a big challenge across resource-rich and limited countries [ 13 , 14 ] that do not allow time to be lost. By the time Graffin study was ordered, the patient's condition changed and passed away before the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the operative management was the most common treatment modality, the current approach to EP treatment in children has shifted towards conservative management [1]. This is especially important in resource limited areas where there is very small number of thoracic pediatric surgeons in addition to the lack facilities [10].…”
Section: Discussionmentioning
confidence: 99%